PENGARUH TEKNOLOGI DIGITAL PADA PEMBENTUKAN KARAKTER PESERTA DIDIK DI SEKOLAH DASAR - sundahry sundahry; Fachruddiansyah Muslim; Ade Kusmana (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
In the current era of digital technology, technological developments cannot be avoided. Technology also has positive and negative influences on students in elementary schools. The negative influence of technology will have an impact on the character of students, of course here the role of parents and teachers needs to be expected so that students are not negatively influenced by the use of technology. The research method used is qualitative research, which means the author only uses journal theory as a reference in writing this article. The aim of the research is to find out how the digital era of technology influences the character formation of students in elementary schools. Based on the research results, the author found that in the current era of digital technology it greatly influences the character formation of students which has a negative impact, especially on elementary school students, causing students to become addicted to playing with gadgets and accessing the internet so they can spend time just playing with gadgets. This causes inadequate performance in carrying out other activities such as studying and playing with peers and also has an impact on children's growth and development and vision problems